The ideological consideration of politics and 11religion in E.M. forster's a passage to India: a Malay perspective - Ahmad Muhyiddin Yusof; Saad Jumaa Farhan; Amalia Qistina Castañeda Abdullah; Muhammad Izzat Rahim; Changting, Li (Penerbit Universiti Kebangsaan Malaysia, 2024)
This paper aims to explore the diverse interpersonal connections portrayed in E.M. Forster's "A Passage to India" through a close examination. The novel depicts British as one nation and the Indians as the colonies, highlighting their attitudes towards each other. By probing into the initial inquiries posed to certain Indian characters, this study endeavours to address a significant query. The primary focus lies in scrutinising the varied relationships developed within the narrative. Some commentators have critiqued Forster's portrayal, suggesting that he critiques the dynamics between colonisers and the colonised. This parallels themes were often found in Malay colonial literary discourse as well, which frequently delve into power dynamics and cultural conflicts between Malays and colonial powers like the British. The study suggests that many relationships falter due to inhospitable conditions. Ultimately, it concludes that individuals often face failure when confronted with uncontrollable external forces. Despite this, the possibility of friendship between equals is affirmed, though acknowledging the disparities between the British and Indians depicted in the novel's timeframe.